Work Duration and Sleep Quality Among Young Workers (A Study In Coffee Shops In West Denpasar District) - Adi Saputra; Alifa Anisa Putri (Publikasi Indonesia, 2024)
This study aimed to describe the work duration and sleep quality among young workers, conducted in coffee shops in the West Denpasar area in 2023. This study employed a quantitative descriptive method with an observational study design and a cross-sectional approach. The sample consisted of 56 coffee shop workers in the West Denpasar area. The variables in this study included the age of workers, work duration, and sleep quality. Data collection was done using primary data through a questionnaire instrument, and data analysis involved descriptive statistical tests. The research results showed that the average age of workers was 20.39 years, with the youngest worker being 18 years old and the oldest 24 years old. The majority of workers had poor sleep quality (80.4%) and worked with a duration of ≥40 hours per week (83.9%). This study concludes that young workers mostly work for ≥40 hours per week and have poor sleep quality. These findings indicate that the conditions of young workers have high-risk factors that could potentially trigger workplace accidents.